EFFECTS OF MICROWAVE-ASSISTED EXTRACTION ON SAPONIN CONTENT FROM Schefflera heptaphylla - relv; Tran Thi Thuy Nhi; Nguyen Cam Huong; Vu Hoang Yen; Ngo Duy Anh Triet; Pham Thi Cam Hoa (HUIT Journal of Science, 2025)
This study was conducted to determine the factors affecting the extraction yield of saponins from Schefflera heptaphylla. Surveyed factors include type of solvent (methanol, ethanol, water), material/solvent ratios (1/15, 1/20, 1/25, 1/30, and 1/35, w/v), microwave powers (150, 300, 450, 650, and 800 W) and microwave times (30, 60, 90, 120 and 150 sec). The extraction yield was shown by the saponin content obtained by UV-Vis spectroscopy. From there, optimize the saponin extraction conditions such as solvent/material ratio, microwave power, and time by response surface method (RSM). The results showed that at optimal conditions, the ratio of material/solvent ratio was 1/25 (w/v), microwave power 360.06W and 110.29 sec, and the obtained saponin content was 52.67 (mg/gdb).